Foxf2 and Smad6 co‐regulation of collagen 5A2 transcription is involved in the pathogenesis of intrauterine adhesion. Issue 5 (5th February 2020) - Chen, Guobin; Liu, Limin; Sun, Jing; Zeng, Liying; Cai, Huihua; He, Yuanli
Abstract: The replacement of normal endometrial epithelium by fibrotic tissue is the pathological feature of intrauterine adhesion (IUA), which is caused by trauma to the basal layer of the endometrium. COL5A2 is a molecular subtype of collagen V that regulates collagen production in fibrotic tissue. Here, we investigated the roles of Foxf2 and Smad6 in regulating the transcription of COL5A2 and their involvement in the pathogenesis of IUA. Small interference‐mediated Foxf2 (si‐Foxf2) silencing and pcDNA3.1‐mediated Smad6 (pcDNA3.1‐Smad6) up‐regulation were performed in a TGF‐β1‐induced human endometrial stromal cell line (HESC) fibrosis model. Assessment of collagen expression by Western blotting, immunofluorescence and qRT‐PCR showed that COL5A2, COL1A1 and FN were significantly down‐regulated in response to si‐Foxf2 and pcDNA3.1‐Smad6. Transfection of lentivirus vector‐Foxf2 (LV‐Foxf2) and pcDNA3.1‐Smad6 into HESCs and qRT‐PCR showed that Foxf2 promoted COL5A2 expression and Smad6 inhibited Foxf2‐induced COL5A2 expression. Co‐immunoprecipitation, chromatin immunoprecipitation and dual‐luciferase reporter assays to detect the interaction between Foxf2 and Smad6 and their role in COL5A2 transcription showed that Foxf2 interacted with Smad6 and bond the same promoter region of COL5A2. In a rat IUA model, injection of ADV2‐Foxf2‐1810 and ADV4‐Smad6 into the uterine wall showed that Foxf2 down‐regulation and Smad6 up‐regulation decreased fibrosis and the expression of COL5A2 and COL1A1, as detected by haematoxylin/eosin, Masson trichrome staining and immunohistochemistry. Taken together, these results suggested that Foxf2 interacted with Smad6 and co‐regulated COL5A2 transcription in the pathogenesis of IUA, whereas they played opposite roles in fibrosis.